2020
DOI: 10.1080/17453674.2020.1827523
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of performance on outcomes after total hip and knee arthroplasty among Dutch orthopedic surgeons: how to improve feedback from arthroplasty registries

Abstract: Background and purpose — The Netherlands Registry of Orthopedic Implants (LROI) uses audit and feedback (A&F) as the strategy to improve performance outcomes after total hip and knee arthroplasty (THA/TKA). Effectiveness of A&F depends on awareness of below-average performance to initiate improvement activities. We explored the awareness of Dutch orthopedic surgeons regarding their performance on outcomes after THA/TKA and factors associated with this awareness. Methods — An anonymous questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The intervention was designed based on evidence regarding effective feedback19 21–23 for orthopaedic surgeons20 and included the following components:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention was designed based on evidence regarding effective feedback19 21–23 for orthopaedic surgeons20 and included the following components:…”
Section: Methodsmentioning
confidence: 99%
“…Worldwide, arthroplasty registries include different performance indicators in their feedback, with revision most commonly used 7 11–18. A recent study showed that Dutch orthopaedic surgeons would like to receive feedback not just on revisions but also on readmission, complications and LOS 20. For arthroplasty surgery, even a relatively small absolute improvement will have huge impact considering the large annual number of THA and TKA performed worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Reminders were sent 1 and 2 weeks after the first invitation, resulting in a response rate of 39%. The final ordering was based on the mean number of points assigned per indicator across respondents: ( 1 ) long LOS (1.1 points); ( 2 ) complications (2.5 points); ( 3 ) readmission (2.6 points) and ( 4 ) revision (3.9 points). This ordering seems to be supported by previous studies, showing that complications during admission (resulting in long LOS) did not affect patient quality of care evaluation, while complications after discharge (resulting in readmission) did, suggesting that patients consider readmissions to be worse than long LOS ( 11 , 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…As quality of care covers different domains such as effectiveness, safety, and efficiency, these are measured with additional indicators ( 2 ). This is acknowledged in a recent Dutch study showing that orthopedic surgeons would like to receive feedback not only on revision, but also regarding readmission, complications, and length of stay (LOS) for hospital comparisons and to monitor the quality of care delivered ( 3 ). The rationale is that benchmarking and feedback may spur quality improvement initiatives in case of suboptimal performance.…”
mentioning
confidence: 99%
“…In addition, scientific articles are published for quality improvement purposes; for example, hospitals are benchmarked, ranked, or (statistical) methods are compared to monitor the quality of care delivered (9,10,11,12,13). The most commonly used quality indicators in this context are implant revision, readmission, and complications, as these indicators are considered reliable, actionable, and fit for purpose (14,15,16,17,18,19). However, the reliability of hospital rankings has been shown to be affected by for example, minor registration incompleteness in the outcome and low event rates, with particularly low volume providers being less likely to become an outlier in funnel plots (11,13).…”
Section: Introductionmentioning
confidence: 99%